Academic identities and university faculty responses to new managerialist reforms: experiences from China. Issue 1 (2nd January 2018) - Huang, Yating; Pang, Sun-Keung; Yu, Shulin
Abstract : Chinese universities are being continually subjected to new managerial practices and technologies that have fundamental consequences on the university faculty's academic life. Within a predominantly communitarian theoretical framework of academic identity, this qualitative case study draws upon interviews with 25 academics in Mainland China to expose the extent to which Chinese academics' values, beliefs and behaviour are convergent and consistent with those that might be expected within the reform agenda. The systematic data analysis identified six identity-related characterisations of how Chinese university faculty at this case university have reacted to this shifting context, contributing to the global literature on the academic profession in two respects. First, it contributes to the empirically grounded knowledge of the complex manner in which Chinese academics negotiate, challenge or comply with the new managerialist agenda. Second, it explores the prime academic identity that Chinese academics have built up under this new managerial circumstances.